INTEGRASI SPIRITUALITAS DALAM MANAJEMEN PENGEMBANGAN KOMPETENSI GURU - Ahmad Rofiqi Tanzil; Ziyadul Ifdhal Ghazali; Ipung Rakandana (lembaga Sepercenter, 2025)
This study aims to analyze the importance of integrating spiritual values into teacher competency development management in the modern education era. Until now, the focus of teacher competency development has been more directed at improving pedagogical, professional, social, and technical personality skills, while the spiritual dimension as a moral and ethical foundation is often neglected. Through a qualitative approach using a literature study method, this study examines various relevant literature related to the relationship between spirituality, educational management, and teacher professional competency. The results of the analysis show that spirituality plays an important role in shaping teachers' self-awareness, intrinsic motivation, and ethical commitment to their profession. The integration of spirituality in competency development management can be done through the formulation of value-based vision and mission, reflective activities and character training, as well as evaluations that emphasize moral aspects and behavioral transformation. Thus, spirituality is not merely an addition, but an essential element that guides the holistic development process of teachers. The implementation of spirituality integration is expected to produce teachers who are professional, have integrity, and possess transcendental awareness in carrying out their duties as educators and shapers of the nation's character.